Evaluasi Persediaan Bahan Baku Dengan Menggunakan Pendekatan Metode Continuous Review System Dan Periodic Review System - Annisa Indah Pratiwi; Amelia Nur Fariza; Ramdani Awaludin Yusup (OPSI, 2020)
Planning and controlling the raw material inventory is carried out in such a way as to meet the needs of raw materials appropriately and at low cost. The problem with plate raw materials is that there is no appropriate method of controlling raw material supplies. Control of raw materials at this company is sometimes erratic due to unstable market demand. Experiencing an accumulation of raw materials when product demand decreases and there is a shortage of raw materials when product demand increases. This study aims to determine a probabilistic inventory model that is good for determining the order quantity, ordering time and safety stock by considering the minimum total cost. Based on the analysis and calculation results, the total inventory cost according to company policy is Rp. 14,734,832 / year, the total cost of the Q model is Rp. 16,300,517 / year with q value of 1,484, r is 965, ss 104, α of 0.013 and S of 2.449 and the total cost of inventory in the P model is Rp.6,384,473 / year with a T value of 0.019, R of 2.264, ss of 105 and α of 0.013. The results show that the Periodic Review System inventory model has an optimal total cost of inventory. Keywords: Inventory Control; Continuous Review System; Periodic Review System; Probabilistic.